Maria Callas een leven als een Griekse tragedie ; biografie - Zoggel, Karl H. van; Puccini, Giacomo 1858-1924; Bellini, Vincenzo 1801-1835; Puccini, Giacomo 1858-1924; Puccini, Giacomo 1858-1924; Wagner, Richard 1813-1883 (Tirion, 2002)
Biografie van de Grieks-Amerikaanse operazangeres (1923-1977); met audio-cd.